A=(+8)-(-4)+(-3)-(+7)=

B=(-9)-(+5)-(-4)+(+8)=

C=(+6)+(-4)+(-7)-(+3)=

D=(-12)-(+8)-(-11)-(+4)=

E=(-5)-(+7)-(-3)+(+11)=

F=(+4)+(-3)+(-6)+(+3)=

G=(-2)+(-1)-(+4)+(-3)-(-8)=

H=(+11)-(+3)+(-4)-(+2)+(-13)=

I=(-25)-(+17)-(-13)+(+21)=

J=(+14)+(-33)+(-16)+(+42)=

K=(-23)+(-31)-(+44)+(-36)-(-28)=

L=(+18)-(+34)+(-14)-(-27)+(-35)=

2

Réponses

  • Utilisateur Brainly
2014-03-01T12:43:50+01:00
Bonjour, 

A=(+8)-(-4)+(-3)-(+7)=
A= 8 + 4 - 3 - 7 
A= 2

B=(-9)-(+5)-(-4)+(+8)
B= -9 + 5 + 4 + 8
B= 8

C=(+6)+(-4)+(-7)-(+3)
C= 6 - 4 - 7 - 3
C= - 8

D=(-12)-(+8)-(-11)-(+4)
D= -12 - 8 + 11 - 4
D= -13

E=(-5)-(+7)-(-3)+(+11)
E= -5 - 7 + 3 +11
E= -2

F=(+4)+(-3)+(-6)+(+3)
F= 4 - 3 - 6 + 3
F= -2

G=(-2)+(-1)-(+4)+(-3)-(-8)
G= -2 - 1 - 4 - 3 + 8
G= -2

H=(+11)-(+3)+(-4)-(+2)+(-13)
H= 11 - 3 - 4 - 2 - 13
H= -11

I=(-25)-(+17)-(-13)+(+21)
I= -25 - 17 + 13 + 21
I= -8

J=(+14)+(-33)+(-16)+(+42)
J= 14 - 33 - 16 + 42
J= 7

K=(-23)+(-31)-(+44)+(-36)-(-28)
K= -23 - 21 - 44 - 36 + 28
K= -86

L=(+18)-(+34)+(-14)-(-27)+(-35)
L= 18 - 34 - 14 + 27 - 35
L= -38

Bonne journée
Désole, la B= -9 - 5 + 4 + 8 = -2 et la E= -12 +14 = 2 :)
2014-03-01T12:44:31+01:00

A= (+8) - (-4) + (-3) - (+7)

A= 8 + 4 - 3 - 7 A= 12 - 3 - 7

A= 9 - 7

A= 2


B= (-9) - (+5) - (-4) + (+8)

B= -9 - 5 + 4 + 8

B= -14 + 4 + 8

B= -10 + 8

B= -2


C= (+6) + (-4) + (-7) - (+3)

C= 6 - 4 - 7 - 3

C= 2 - 7 - 3

C= -5 - 3

C= -8


D= (-12) - (+8) - (-11) - (+4)

D= -12 - 8 + 11 - 4

D= -20 + 11 - 4

D= -9 - 4

D= -13


E= (-5) - (+7) - (-3) + (+11)

E= -5 - 7 + 3 + 11

E= -12 + 3 + 11

E= -9 + 11

E= 2


F= (+4) + (-3) + (-6) + (+3)

F= 4 - 3 - 6 + 3

F= 1 - 6 + 3

F= -5 + 3

F= -2


G= (-2) + (-1) - (+4) + (-3) - (-8)

G= -2 - 1 - 4 - 3 + 8

G= -3 - 4 - 3 + 8

G= -7 - 3 + 8

G= -10 + 8

G= -2


H= (+11) - (+3) + (-4) - (+2) + (-13)

H= 11 - 3 - 4 - 2 - 13

H= 8 - 4 - 2 - 13

H= 4 - 2 - 13

H= 2 - 13

H= -11


I= (-25) - (+17) - (-13) + (+21)

I= -25 - 17 + 13 + 21

I= -42 + 13 + 21

I= -29 + 21

I= -8


J= (+14) + (-33) + (-16) + (+42)

J= 14 - 33 - 16 + 42

J= -19 - 16 + 42

J= -35 + 42

J= 7


K= (-23) + (-31) - (+44) + (-36) - (-28)

K= -23 - 31 - 144 - 36 + 28

K= -54 - 144 - 36 + 28

K= -198 - 36 + 28

K= -234 + 28

K= -206


L= (+18) - (+34) + (-14) - (-27) + (-35)

L= 18 - 34 - 14 + 27 - 35

L= -16 - 14 + 27 - 35

L= -30 + 27 - 35

L= -3 - 35

L= -38